New fluorinated rhodamines for optical microscopy and nanoscopy. - Mitronova, G; Belov, V; Bossi, M; Wurm, C; Meyer, L; Medda, R; Moneron, G; Bretschneider, S; Eggeling, C; Jakobs, S; Hell, S (2010)
New photostable rhodamine dyes represented by the compounds 1 a-r and 3-5 are proposed as efficient fluorescent markers with unique combination of structural features. Unlike rhodamines with monoalkylated nitrogen atoms, N',N-bis(2,2,2-trifluoroethyl) derivatives 1 e, 1 i, 1 j, 3-H and 5 were found to undergo sulfonation of the xanthene fragment at the positions 4' and 5'. Two fluorine atoms were introduced into the positions 2' and 7' of the 3',6'-diaminoxanthene fragment in compounds 1 a-d, 1 i-l and 1 m-r. The new rhodamine dyes may be excited with λ=488 or 514 nm light; most of them emit light at λ=512-554 nm (compounds 1 q and 1r at λ=576 and 589 nm in methanol, respectively) and have high fluorescence quantum yields in solution (up to 98 %), relatively long excited-state lifetimes (>3 ns) and are resistant against photobleaching, especially at high laser intensities, as is usually applied in confocal microscopy. Sulfonation of the xanthene fragment with 30 % SO3 in H2SO4 is compatible with the secondary amide bond (rhodamine-CON(Me)CH2CH2COOH) formed with MeNHCH2CH2COOCH3 to providing the sterically unhindered carboxylic group required for further (bio)conjugation reactions. After creating the amino reactive sites, the modified derivatives may be used as fluorescent markers and labels for (bio)molecules in optical microscopy and nanoscopy with very-high light intensities. Further, the new rhodamine dyes are able to pass the plasma membrane of living cells, introducing them as potential labels for recent live-cell-tag approaches. We exemplify the excellent performance of the fluorinated rhodamines in optical microscopy by fluorescence correlation spectroscopy (FCS) and stimulated emission depletion (STED) nanoscopy experiments.